Charmed Again - Lenhard, Elizabeth (London Simon & Schuster UK Ltd., 2002)
While mourning the death of their sister, Prue, Phoebe and Piper learn of the existence of a half-sister called Paige.
Keywords: Witches -- Sisters -- Paranormal fiction